2018
DOI: 10.1158/1055-9965.epi-17-0727
|View full text |Cite
|
Sign up to set email alerts
|

TSH, Thyroid Hormone, and PTC—Letter

Abstract: Huang and colleagues (1) reported on the relationship between papillary thyroid cancer risk and prediagnostic levels of thyroidstimulating hormone (TSH) and lent support to our previous findings (2) on the existence of an inverse association. The two studies were case-control studies nested in very different populations, that is, U.S. military staff mainly below age 50 years (400 male and 341 female cases; ref. 1) and healthy volunteers from the European Prospective Investigation in Cancer and Nutrition cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies have led to inconsistent conclusions on the relationship between TSH levels and thyroid cancer risk 8 . Several studies have observed an association between low TSH levels, which can occasionally occur as a consequence of autonomous thyroid nodules and an increased risk of thyroid cancer [8][9][10][11][12][13] . In contrast, several studies have indicated that TSH promotes the growth of thyroid cancers 8, [14][15][16] , which has led to the recommendation to lower TSH levels among people with thyroid cancer to reduce the risk of cancer recurrence.…”
mentioning
confidence: 99%
“…Previous studies have led to inconsistent conclusions on the relationship between TSH levels and thyroid cancer risk 8 . Several studies have observed an association between low TSH levels, which can occasionally occur as a consequence of autonomous thyroid nodules and an increased risk of thyroid cancer [8][9][10][11][12][13] . In contrast, several studies have indicated that TSH promotes the growth of thyroid cancers 8, [14][15][16] , which has led to the recommendation to lower TSH levels among people with thyroid cancer to reduce the risk of cancer recurrence.…”
mentioning
confidence: 99%